Neglect of Street Vendors (PKL) Towards the Jayapura City Government Regulations on Public Order During the Covid-19 Pandemic - Amirullah Amirullah; Akbar Jaya (JOURNAL OF SHARIA ECONOMICS, 2022)
This study examines the neglect of street vendors (PKL) in adhering to the Jayapura City Government's regulations on public order during the Covid-19 pandemic. The research highlights the challenges faced by the government in enforcing public order rules and the underlying factors contributing to the non-compliance of PKL. Using a qualitative approach, data was gathered through interviews, observations, and documentation involving street vendors, local authorities, and community representatives. The findings reveal that the neglect stems from economic pressures, lack of awareness, and inadequate socialization of the regulations. Many street vendors prioritized their livelihood over compliance with public order measures, exacerbating public health risks during the pandemic. The study also identifies gaps in the government's strategies, including insufficient enforcement and the absence of alternative solutions for the affected vendors. Recommendations are provided to enhance regulatory compliance, including improved communication, provision of economic support, and collaboration with community leaders to ensure public order while safeguarding livelihoods. This research contributes to understanding the dynamics of policy compliance among vulnerable groups during crises and offers insights for policymakers in similar contexts.